14-3-3zeta is involved in the anticancer effect of metformin in colorectal carcinoma. (30th January 2018) - Ding, Jing; Zhu, Yue-Ting; Yang, Lie; Tang, Jie; Wang, Yu-Yi; Chen, Ye; Cheng, Ke; Liu, Jia-Qi; Zhang, Yun-Ni; Li, Zhi-Ke; Du, Yang; Qiu, Meng; et al.
Abstract : Metformin may cancel the AMP-dependent protein kinase inhibition caused by 14-3-3zeta in colorectal cancer. Our study is helpful for understanding the anticancer activity of metformin and also implies the possible application of metformin in cancers with high expression level of 14-3-3zeta. Abstract: Metformin is a promising drug for cancer prevention and treatment, especially in the diabetic population. We aimed to test whether 14-3-3zeta affects the anticancer effect of metformin on colorectal carcinoma (CRC). In this study, we confirmed that higher 14-3-3zeta expression was found in CRC tissues than in pericarcinoma tissues, and in CRC tissue of patients with diabetes than in those without diabetes. A knockdown of 14-3-3zeta inhibited CRC proliferation and promoted apoptosis in vitro and in vivo . Then, we created stable cell lines with under-expressed 14-3-3zeta from SW480 and HCT15 cells after infection by a lentiviral vector carrying short hairpin RNA targeting 14-3-3zeta (named LV-sh14-3-3zeta). Of note, metformin induced apoptosis and retarded tumor growth in the CRCs with overexpressed 14-3-3zeta, whereas this action was attenuated when 14-3-3zeta was knocked down. Moreover, either metformin or downregulation of 14-3-3zeta noticeably activated AMP-dependent protein kinase (AMPK) signaling, whereas the effect of metformin was attenuated when the 14-3-3zeta expression was decreased. Taken together, our results suggest that 14-3-3zeta may be associated with carcinogenesis and poor prognosis of CRCs associated with diabetes, and metformin may reverse the AMPK inhibition caused by 14-3-3zeta in CRCs in the background of diabetes. Our study should lead to a better understanding of the anticancer activity of metformin and points to possible application of metformin to the treatment of cancers overexpressing 14-3-3zeta.